2015
DOI: 10.12659/msm.892768
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Tranexamic Acid for Total Knee Arthroplasty: A Prospective Randomized Controlled Trial

Abstract: BackgroundTotal knee arthroplasty (TKA) is associated with significant perioperative blood loss and need for transfusion. This study aimed to evaluate the effectiveness and safety of tranexamic acid (TXA) to reduce perioperative blood loss in patients receiving TKA.Material/MethodsA total of 92 patients who accepted unilateral TKA from May 2012 to May 2013 randomly received either 15 mg/kg TXA in 100 mL normal saline solution (TXA group, n=46) or the same amount of normal saline solution (placebo group, n=46) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 19 publications
1
29
0
2
Order By: Relevance
“…There is growing evidence for the well tolerated and beneficial use of tranexamic acid to reduce perioperative blood loss, allogeneic blood transfusions and associated costs in major orthopaedic surgery such as total hip or knee arthroplasty, and spine surgery. [313][314][315][316][317][318][319][320][321][322][323][324][325][326] However, tranexamic acid is not recommended in patients with hypersensitivity or allergy to the drug, history of venous or arterial thrombosis, or thrombophilia, cardiovascular disease, acute renal failure or subarachnoid haemorrhage, or in patients with a history of seizures or epilepsy. 327 There is emerging evidence that topical administration of tranexamic acid may be beneficial in reducing the rate of blood transfusions in both total hip replacement and total knee replacement surgery.…”
Section: Antifibrinolyticsmentioning
confidence: 99%
“…There is growing evidence for the well tolerated and beneficial use of tranexamic acid to reduce perioperative blood loss, allogeneic blood transfusions and associated costs in major orthopaedic surgery such as total hip or knee arthroplasty, and spine surgery. [313][314][315][316][317][318][319][320][321][322][323][324][325][326] However, tranexamic acid is not recommended in patients with hypersensitivity or allergy to the drug, history of venous or arterial thrombosis, or thrombophilia, cardiovascular disease, acute renal failure or subarachnoid haemorrhage, or in patients with a history of seizures or epilepsy. 327 There is emerging evidence that topical administration of tranexamic acid may be beneficial in reducing the rate of blood transfusions in both total hip replacement and total knee replacement surgery.…”
Section: Antifibrinolyticsmentioning
confidence: 99%
“…similarly, Maniar et al, also in a randomized controlled trial, demonstrated that a three-dose regimen (adding a postoperative dose) may be even more effective (32). Most of the studies confirmed the efficacy of different doses of iV tXA in reducing transfusion rates and total blood loss (27,(33)(34)(35)(36)(37)(38)…”
Section: Discussionmentioning
confidence: 90%
“…Интраоперационная кровопотеря неминуемо приводит к усугублению имеющейся анемии в послеоперационном периоде [5], т. е. состояния, которое требует трансфузии компонентов крови [6]. Это, в свою очередь, удлиняет средний срок пребывания больного в стационаре и увеличивает стоимость лечения [7].…”
Section: пластическая и реконструктивная хирургияunclassified